Penguatan Keagamaan Mualaf Melalui Metode Komunikasi Dakwah Pada Masyarakat Suku Akit Provinsi Riau - Nurjanah Nurjanah; Maha Recha Sucita Nanda (MENARA RIAU, 2022)
The function of da'wah is to spread Islam to mankind as members of society so that they have good morals and behavior according to Islamic guidance. The method of delivering da'wah is important so that what is conveyed is true and correct. This service aims to foster Akit Tribe converts, through da'wah communication and interpersonal communication as a medium of learning that is carried out in fostering converts to converts at Rumah Saudara Baru. The subject of this service activity consisted of 8 converts to Islam with an observation, interview, and documentation approach. The results of the service show that the development of Akit tribe converts uses lecture, demonstration, question and answer, and discussion methods, analyzed using Fritz Heider's Attribution theory. Interpersonal communication and group communication patterns include reading the Qur'an and religious lectures. Seen based on the direction of information that is circle pattern and chain pattern. Both are described in accordance with the form of activity, messages through the communication media of the coach. The results of the service are used as input for fostering converts to Islam to develop more interesting and varied learning methods in the future.